2021
DOI: 10.1002/slct.202004427
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight‐Assisted Photocatalytic Sustainable Synthesis of 1,4‐Disubstituted 1,2,3‐Triazoles and Benzimidazoles Using TiO2−Cu2(OH)PO4 Under Solvent‐Free Condition

Abstract: Herein, we report the facile synthesis of 1,4‐disubstituted 1,2,3‐triazoles and benzimidazoles using TiO2−Cu2(OH)PO4 as an efficient sunlight active nanophotocatalyst under solvent‐free condition. The highlights of the proposed protocol are simple, scalable with a broad substrate scope, short reaction time, excellent regioselectivity and catalyst recyclability. The use of recyclable photocatalyst and solvent‐free condition makes the catalytic system resulted in sustainable and environmental‐friendly procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Having obtained CuO NRs successfully with rewarding catalytic properties, we next intend to explore their scope toward azide–alkyne cycloaddition to prepare triazoles. Based on our previous endeavor in triazolylation by CuO catalysis, we initially checked the feasibility of the desired chemistry in prototype substrates using commercially viable CuO (Table ). To this end, the catalytic process begins with the reaction between benzyl azide ( 1a , 1.5 mmol), phenyl acetylene ( 2a , 1.0 mmol), and CuO bulk (10 mol %) in water (5 mL) at room temperature, which produces 1,4-disubstituted 1,2,3-triazole 3a in 20% yield after 24 h (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having obtained CuO NRs successfully with rewarding catalytic properties, we next intend to explore their scope toward azide–alkyne cycloaddition to prepare triazoles. Based on our previous endeavor in triazolylation by CuO catalysis, we initially checked the feasibility of the desired chemistry in prototype substrates using commercially viable CuO (Table ). To this end, the catalytic process begins with the reaction between benzyl azide ( 1a , 1.5 mmol), phenyl acetylene ( 2a , 1.0 mmol), and CuO bulk (10 mol %) in water (5 mL) at room temperature, which produces 1,4-disubstituted 1,2,3-triazole 3a in 20% yield after 24 h (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the aforementioned context, cupric oxides in various nanodimensions have been frequently encountered as a heterogeneous catalyst for triazolylation owing to their well-understood physicochemical properties, environmentally friendly appeal, and facile recyclability. However, controlling the size and shape is a complicated combination of various interlinking factors such as steric confinements, temperature, and electrostatic interactions. Nevertheless, different modes of preparation for CuO nanomaterials have been documented, depending on which, the morphology and size can be fine-tuned. In terms of simplicity, chemical coprecipitation is by far the most popular method, as it does not employ any reducing agents, support materials, or immobilizing agents. With this background coupled with our pursuit on azide–alkyne cycloaddition by CuO-based nanocatalysis, we herein report a simple synthesis of nanorod-like cupric oxide (referred throughout as CuO NRs) by adopting the coprecipitation strategy. Compared to other established procedures, our coprecipitation strategy enables the formation of CuO nanoparticles in high aspect ratio (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the results suggested that the photocatalytic conversion process was well compatible with the substituents no matter they are electron‐withdrawing or ‐releasing groups, such as −OH, −Cl, −Br, −NO 2 . They had little effect on the yield of BIs [15,37,43] . Some other studies showed that the activity of aromatic aldehydes with electrophilic substituents was slightly higher than that with electron‐donating substituents [16–17,23,42] .…”
Section: The Effect Of Reaction Conditions On the Yield Of Bismentioning
confidence: 94%
“…Compositing TiO 2 with other semiconductors or functional components is the third effective way to enhance its performance for BIs synthesis as these components can improve the separation of photoinduced charge carriers, the adsorption of reactants, and can extend the light absorption range of TiO 2 . A composite TiO 2 /Cu 2 (OH)PO 4 photocatalyst was prepared by Kiranmye et al [37] . and used as an efficient sunlight photocatalyst for synthesis of BIs under solvent‐free condition with OPDA and aromatic aldehyde as reactants (Scheme 10).…”
Section: Heterogeneous Photocatalytic Synthesis Of Bismentioning
confidence: 99%
See 1 more Smart Citation